Cardiopulmonary effects of anaesthesia maintained by propofol infusion versus isoflurane inhalation in cheetahs (Acinonyx jubatus). (November 2017) - Buck, Roxanne K.; Tordiffe, Adrian SW.; Zeiler, Gareth E.
Abstract: Objective: To compare the cardiopulmonary effects of propofol total intravenous anaesthesia (TIVA) with isoflurane in cheetahs ( Acinonyx jubatus ) to evaluate feasibility for field use. Study design: Prospective clinical study. Animals: A group of 24 adult cheetahs, 12 per group. Methods: Cheetahs were immobilized with zolazepam/tiletamine (1.2 mg kg −1 ) and medetomidine [40 μg kg −1, both intramuscular (IM)] by darting. A maintenance protocol of propofol TIVA (group P) or isoflurane inhalation (group I) was assigned randomly to each cheetah. Anaesthesia was maintained for at least 60 minutes. Cheetahs breathed spontaneously throughout; oxygen was supplemented at 3 L minute −1 . Cardiopulmonary parameters were recorded at 5 minute intervals and three arterial blood gas samples were analysed. Following maintenance, atipamezole was administered IM (200 μg kg −1 ) and recovery was observed. Data are reported as mean ± standard deviation; variables over time were compared using a linear mixed model (fixed: time, treatment; random: cheetah). Results: Lack of response to manipulations was maintained in all cases (end-tidal isoflurane percentage 1.1 ± 0.1%, propofol rate maintained at 0.1 mg kg −1 minute −1 ). The heart and respiratory rates were acceptable throughout maintenance. The end-tidal carbon dioxide tension increased slowly [44.0 ± 5.0 mmHg (5.87 ± 0.67 kPa)] with no differences between groups. All cheetahs were initially markedly hypertensive [mean arterial blood pressure (MAP): (163 ± 17 mmHg)]. The MAP normalized for group I (125 ± 30 mmHg) but remained high for group P (161 ± 17 mmHg) ( p < 0.001). Arterial carbon dioxide tension [48.9 ± 14.6 mmHg (6.52 ± 1.95 kPa)] never differed between groups. Initial arterial oxygen tension indicated borderline hypoxaemia, but improved with oxygen supplementation. Recovery time was 10.8 ± 5.0 and 51.9 ± 23.5 minutes for group I and group P, respectively. Conclusions and clinical relevance: Both protocols provided acceptable cardiopulmonary values. Propofol may be an alternative to isoflurane for field use, but the prolonged recovery may make it less suitable for long-term anaesthesia.